(untitled) (International Journal of Engineering and Computer Science, 2015)
In this paper analysis of a semi-markov model is done with reference to famous Jelinski-Moranda model which is probably the first model in software reliability. Fault removal resulting from the execution of program depends on the occurrence of the associated failure. Occurrence of failure depends both on the length of time for which the software has been executing and on the execution environment or operating condition. When different functions are executed, different faults are encountered and failures that are exhibited tend to be different.